Flaxseed Extract Can Modulates Apoptotic Genes to Promote Cell Death in Breast Cancer Cells - Ehsan Zare Mehrjardi; Shadi Montazerolhojeh; Masoud Dehghan Tezerjani; Safieh Dehshiri; Mahmood Dehghani Ashkezari; Seyed Morteza Seifati (Middle East Journal of Cancer, 2025)
Background: Breast cancer is a multifactorial malignancy with uncertain treatment outcomes, making its treatment challenging. Balanced level of genes expression, including BAX, BCL2L1 (bcl-xl) and BCL-2 are needed to regulate apoptosis pathway in cancers. The aim of this study was to examine the impact of flaxseed extract on the expression of BAX, BCL-2, and BCL2L1 (bcl-xl) gens in BT-474 and MCF-7 breast cancer cells.Method: This in vitro experimental study investigated the impact of flaxseed extract on apoptosis and the proliferation of BT-474 and MCF-7 breast cancer cells. MTT assay was conducted on flaxseed extract treated BT-474 and MCF-7 cells at concentrations 3.90628, 7.8125, 156.125, 312.5, 125, 2, 1000, and 2000 µg/ml for 24, 48 and 72h. IC50 (μg/ml) was calculated for flaxseed extract in both cells. The expression of BCL2L1 (bcl-xl), bcl-2 and Bax genes were evaluated at these concentrations using real time Polymerase Chain Reaction (PCR). The data from different groups were analyzed using the Student's t-test.Results: Flaxseed extract reduced the multiplication and growth of BT-474 and MCF-7 cells in a concentration-dependent manner over 24, 48, and 72 hours of incubation. In both flaxseed-extract exposed BT-474 and MCF-7 cell lines, the BAX gene expression increased (P < 0.05); however, the gene expression of BCL2L1 (bcl-xl) and BCL-2 genes decreased (P < 0.05).Conclusion: Incubating BT-474 and MCF-7 with flaxseed extract repressed their growth and induced apoptosis. These results may provide precious information for developing a plant-based agent to prevent or treat breast cancer.